2019
DOI: 10.1016/j.ebiom.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

HNF1A inhibition induces the resistance of pancreatic cancer cells to gemcitabine by targeting ABCB1

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) is an aggressive disease with poor prognosis, and gemcitabine-based chemotherapy remains an effective option for the majority of PDAC patients. Hepatocyte nuclear factor 1α (HNF1A) is a tumor-suppressor in PDAC, but its role in gemcitabine chemoresistance of PDAC has not been clarified. Methods The function of HNF1A in gemcitabine was detected by overexpression and knockdown of HNF1A in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…The recent study showed that patients with pancreatic ductal adenocarcinoma (PDAC) with the HNF1A-positive subtype had the best prognostic survival time [22]. In a separate study, patients of PDAC in high HNF1A group demonstrated an improvement in OS and DFS compared with the moderate/low HNF1A groups [9]. In contrast, the patients of ESCC with high expression of HNF1A had a poor OS and PFS through online analysing by GEPIA and Kaplan-Meier plotter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent study showed that patients with pancreatic ductal adenocarcinoma (PDAC) with the HNF1A-positive subtype had the best prognostic survival time [22]. In a separate study, patients of PDAC in high HNF1A group demonstrated an improvement in OS and DFS compared with the moderate/low HNF1A groups [9]. In contrast, the patients of ESCC with high expression of HNF1A had a poor OS and PFS through online analysing by GEPIA and Kaplan-Meier plotter.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the overexpression of HNF1A promoted the proliferation of ESCC cells. In several studies, HNF1A had been linked to resistance to chemical drugs, including colon cancer [24] and pancreatic cancer [8][9][10]. However, there was little research on its relationship with radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysfunction of pancreatic beta cells and impaired insulin secretion because of HNF1α or HNF4α mutations are believed to be the pathological mechanisms to this type of disease. In addition to MODY, HNF1α and HNF4α are involved in other type of diseases, including other metabolic diseases, inflammatory diseases, and cancer [52][53][54][55]. HNF1α and HNF4α are reported to play different roles based on cancer types.…”
Section: Genomic Locations and Structures Of Hnf1α-as1 And Hnf4α-as1mentioning
confidence: 99%
“…The most extensively studied ABC transporters related to chemoresistance include ABCB1 (also named P-glycoprotein or multidrug resistant gene 1), ABCC1 (also named multidrug resistance protein 1), and ABCG2 (also named breast cancer resistance protein) 8 . These ABC transporters have been demonstrated to confer PC resistance to gemcitabine (GEM) 9 11 , which is the mainstay chemotherapeutic agent for PC. Several other members of ABCB or ABCC subfamily, such as ABCB2 12 and ABCC5 13 , have also been found to be associated with PC chemoresistance.…”
Section: Introductionmentioning
confidence: 99%